2014
DOI: 10.3892/etm.2014.1742
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various decellularization methods on histological and biomechanical properties of rabbit tendons

Abstract: The aim of the present study was to investigate the effects of various decellularization methods on the histological and biomechanical properties of rabbit tendons. In total, six chemical reagents, including 1% t-octyl-phenoxypolyethoxyethanol (Triton-X 100), 0.5% sodium dodecyl sulfate (SDS), 1% tri-n-butyl phosphate (TnBP), 1% Triton-X 100 + 0.5% SDS, 1% TnBP + 0.5% SDS and 1% TnBP + 1% Triton-X 100, were used on rabbit semitendinosus muscles and flexor digitorum tendons for 24 h to remove cells. Hematoxylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 25 publications
1
29
0
3
Order By: Relevance
“…The decellularization process, in general a combination of mechanical, chemical and enzymatic approaches, has to be accompanied by adequate analytics [17,18] to guarantee the effectiveness of the process and thus the characteristics of the final structure. Consequently, the removal of cells and cellular debris and the conservation of the decellularized tissue matrix in terms of composition and ultrastructure, were evaluated by histology, scanning electron microscopy analysis and an array of biochemical quantification methods.…”
Section: Introductionmentioning
confidence: 99%
“…The decellularization process, in general a combination of mechanical, chemical and enzymatic approaches, has to be accompanied by adequate analytics [17,18] to guarantee the effectiveness of the process and thus the characteristics of the final structure. Consequently, the removal of cells and cellular debris and the conservation of the decellularized tissue matrix in terms of composition and ultrastructure, were evaluated by histology, scanning electron microscopy analysis and an array of biochemical quantification methods.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Several studies of commercially available tendon grafts have reported their biological characteristics and clinical efficacy, but tendon matrices specifically designed for hand tendons are currently unavailable. 6,[8][9][10] The use of animal tendon as a source material for this purpose could lead to an ideal matrix with better overall mechanical properties, and strategies have been tested to process tendon of various species, including rat, 11 porcine, 12,13 canine, rabbit, 14,15 and equine. 16,17 The equine superficial digital flexor tendon (SDFT) presents a potential realistic source for human tendon grafting due to its large dimensions, availability in large quantities, and traceability through accredited food industries.…”
Section: Introductionmentioning
confidence: 99%
“…The decellularization process is aiming to remove almost all of the cellular components that might induce immunogenicity but preserving the structural and biochemical properties. Recently reported methods to make decellularize tissues are more likely to combine the physical, chemical or enzymatic strategies to achieve higher quality dECM scaffold/ biomaterials [11,[20][21][22][23][24][25][26]. We have previously prepared decellularized brain matrix by agitation in the following decellularization baths and completely removed the cellular components with entire brain structure [27,28].…”
Section: Discussionmentioning
confidence: 99%